Therapy of Schizophrenia Disorders with Spiritual Methods at the Az-Zainy Tumpang Mental Rehabilitation Boarding School Malang Regency / Terapi Gangguan Skizofrenia dengan Metode Spritual Di Pesanten Rehabilitasi Mental Az-Zainy Tumpang Kabupaten Malang - Rofiq, Aunur; Anam, Khoirul; Imamudin, Mochamad (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
This study examines the psychiatric disorder Schizophrenia. The researcher took a sample of the research site at the Az-Zainy Tumpang Islamic Boarding School. In this study, it is explained that people who experience schizophrenia are very underestimated by the community and without any action for the healing process. For this reason, the Az-Zainy Islamic boarding school is one of the places for therapy for the healing process of students who have schizophrenia. With the care of KH. Zain Baik, the method of healing is by using prayer and ruqyah, namely asthma and hizb. With this research, it is hoped that it can provide insight for readers, that spiritual therapy using prayer and ruqyah methods can heal students who experience mental disorders, especially Schizophrenia. For this reason, in taking research data, researchers use descriptive-qualitative research methods with field observation research models, interviews with research objects, written data, documentation as evidence from field research. So that the four models can provide accuracy in this study. This research study resulted in an analysis that people with Schizophrenia disorder can be cured by the therapeutic process that has been carried out by KH. Zain Good. The healing process does not require a short time but also takes a long time in the healing process. Besides the therapy that has been done by KH. Zain Baik, students are also introduced to learning calistung, reciting the Koran, etc., so that students who are starting to recover can recall reading letters with their own abilities.Â Keyword: Therapy, Schizophrenia, Prayer, Ruqyah